The Analysis of Influence of Acoustic Signal Reflection in Pipelines to Correlation Function of these Signals - Jakevicius, L.; Tumsys, O.; Gudavicius, G. (Elektronika ir Elektrotechnika, 1997)
There was analysed the influence of reflections of acoustic signals from bendings and ends of the pipelines to intercorrelation functions of these signals. It was shown that in measurements of coordinates of nonhermetic places of the pipelines using the maxima of correlation curve, we must evaluate the places of the reflections of acoustic signals and choose the places of attachment of transducers, in such a way that number of maxima of correlation function would be reduced to the minimum.